Association between schizophrenia and homozygosity at the dopamine D3 receptor gene. Issue 12 (December 1992) - Crocq, M A; Mant, R; Asherson, P; Williams, J; Hode, Y; Mayerova, A; Collier, D; Lannfelt, L; Sokoloff, P; Schwartz, J C
Abstract : Disturbances in dopamine neurotransmission have been postulated to underlie schizophrenia. We report data from two independent studies of a BalI polymorphism in the dopamine D3 receptor gene in patients with schizophrenia. In both studies, more patients than controls were homozygous (p = 0.005, p = 0.008). When pooled data were analysed, this difference was highly significant (p = 0.0001) with a relative risk of schizophrenia in homozygotes of 2.61 (95% confidence intervals 1.60-4.26).